2006
DOI: 10.1111/j.1574-6968.1997.tb12619.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel endo-levanase and its gene from Bacillus sp. L7

Abstract: A novel endo-levanase producing bacterium belonging to the Bacillus family has been isolated from soil. The enzyme was characterized and found to have no exo-beta-fructofuranosidase activity. The endo-levanase gene was cloned and sequenced. Homology searches have shown that the C-terminal domain of the enzyme is homologous to a number of known beta-fructofuranosidases, including exo-levanase from Bacillus subtilis and yeast invertases. The N-terminal region of the endo-levanase which is homologous to the C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Levanases (EC 3.2.1.65) are enzymes found in some microorganisms (e.g., Bacillus and Pseudomonas) that catalyze the hydrolysis of the β-2,6-linked main chain of levan, a natural product from the group of fructans (Murakami et al 1992; Miasnikov 1997). Levan polysaccharide is known to play an ecological role on Bacillus biofilm formation and maintenance (Marvasi et al 2010), while on some strains of Pseudomonas are suggested to be part of a protective capsule against phages (PATON 1960).…”
Section: Diversity Of Phage Depolymerasesmentioning
confidence: 99%
“…Levanases (EC 3.2.1.65) are enzymes found in some microorganisms (e.g., Bacillus and Pseudomonas) that catalyze the hydrolysis of the β-2,6-linked main chain of levan, a natural product from the group of fructans (Murakami et al 1992; Miasnikov 1997). Levan polysaccharide is known to play an ecological role on Bacillus biofilm formation and maintenance (Marvasi et al 2010), while on some strains of Pseudomonas are suggested to be part of a protective capsule against phages (PATON 1960).…”
Section: Diversity Of Phage Depolymerasesmentioning
confidence: 99%
“…In fact, this type of behavior is common to a number of polysaccharide hydrolases, which possess a single catalytic domain linked at either the N-or C-terminus to one or more polysaccharide (ligand) binding sites. 16 Contrary to LMW levan, most of the investigated levanases showed a negative cooperativity in the presence of the HMW levan substrate with Hill coefficients lower than 1. As indicated in Table 4, the maximum rate of levan hydrolysis (v max ) is highly differentiable among the levanases studied.…”
Section: Catalytic Properties Of Selected Levanase Candidatesmentioning
confidence: 98%
“…The last optimum temperature is higher than the other levanases we studied and those previously reported, with the exception of G. diazotrophicus SRT4 (45 °C), 15 Pseudomonas K-52 (70 °C), 22 and Bacillus sp. L7 (50 °C) 16 levanases. Indeed, Lim et al 9 reported 40 °C to be the optimal temperature for Streptomyces sp.…”
Section: Catalytic Properties Of Selected Levanase Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…PSDs collectively have a broad diversity in terms of their substrate specificities [ 18 ], although they can be generally differentiated into two classes: hydrolases and lyases [ 85 ] ( Figure 4 ). The hydrolases catalyze the hydrolysis of glycosidic bonds [ 58 ] and currently include six groups: sialidases (hydrolyzing α-2,8-linkages in capsular polysialic acid) [ 86 ], rhamnosidases (cleaving α-1,3 O-glycosidic bonds between L-rhamnose and D-galactose) [ 87 ], levanases (hydrolyzing β-2,6-bonds between fructose monomers in levan) [ 88 , 89 ], xylanases (cutting β-1,4 bonds within xylan) [ 90 , 91 , 92 , 93 ], dextranases (cleaving α-1,6-linkages between glucose units in dextran) [ 94 , 95 ], and LPS deacetylases (deacetylating the O-antigen) [ 55 , 66 , 96 ]. The lyases instead cleave (1,4) glycosidic bonds by a β-elimination mechanism [ 97 , 98 ] and currently comprise five groups: hyaluronate lyase (cleaving β-1,4 bonds in hyaluronic acid) [ 99 ], pectate lyase (cleaving α-1,4 bonds of polygalacturonic acid) [ 100 , 101 ], alginate lyase (cutting α-1,4 bonds of alginate) [ 102 , 103 ], K5 lyase (cleaving α-1,4 bonds of E. coli K5 capsules) [ 104 ], and O-specific polysaccharide lyase (cleaving of O-specific antigen of LPS) [ 105 ].…”
Section: Phage-encoded Polysaccharide Depolymerases (Psds)mentioning
confidence: 99%